English Language Lacks of Textile and Apparel Fashion Technology Trainees of Ethiopia Technical and Vocational Training Institute - Woret, Gashaw Shewangizaw; Anshu, Alemu Hailu (REiLA : Journal of Research and Innovation in Language, 2024)
This study aimed to investigate the perceptions of English language proficiency and difficulties among trainees at the Federal Democratic Republic of Ethiopia Technical and Vocational Training Institute (TVTI). With English proficiency being increasingly vital for global career success, particularly in technical fields such as textile and apparel fashion, it is crucial to explore the language needs and challenges in the under-researched Ethiopian TVET context. Using a mixed-methods approach, data were gathered from 128 trainees through questionnaires, observations, and interviews. Quantitative data were analyzed using SPSS 24, and qualitative data were analyzed using MAXQDA 24. The results showed that trainees perceived writing and speaking as the most difficult macro-skill. Within writing, tasks like reports and proposals were especially challenging due to issues with organization, structure, and grammar usage. For speaking sub-skills, presentations and describing diagrams became difficult for trainees as these were related to clarity and vocabulary. Comprehension of spoken content in class and taking notes were considered challenging due to rapid speech and accents that were not familiar. When it comes to reading sub-skills, understanding complex and specialized vocabulary was most difficult with technical reports and manuals. Trainees also expressed difficulties in understanding models and instructions. Generally, the results indicate inadequacies in skills needed for future studies and careers. Incorporating language instruction combined with real-world practice in all areas could improve trainees' skills to meet the language requirements of their technical fields.